2006
DOI: 10.1021/la0528448
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organization of Amide Dendrons and Their Dendronized Macromolecules

Abstract: A polymerizable methacryl unit was introduced at the focal moiety of the amide dendrons which have amide branches and alkyl periphery. Their dendronized polymers were also prepared by the radical polymerization of the methacryl units. The self-organization characteristics of dendrons and dendronized polymers were then investigated in both the organic and aqueous phases. The amide dendrons (1M and 2M) in which the focal carboxyl group was blocked with methacryl units did not form gel in organic media such as ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…16,17 The resulting polyelectrolyte-surfactant complexes have been shown to microphase segregate into liquid crystalline mesophases, analogous to those obtained in systems where the mesogenic units are covalently attached to macromolecules. [18][19][20][21][22][23][24] Bioinspired complexes based on ionic complexation of polypeptides and phospholipids have been recently reported using both peptide homopolymers and block copolymers, leading to a rich polymorphism, including lamellar, tetragonal 14,15 or rectangular 14,25 mesophases. Furthermore, in contrast to peptidic polymers covalently modified with mesogenic units, 26,27 polypeptide-surfactant complexes are expected to be pH responsive and thus offer a very promising pathway to design pH-responsive mesostructures.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The resulting polyelectrolyte-surfactant complexes have been shown to microphase segregate into liquid crystalline mesophases, analogous to those obtained in systems where the mesogenic units are covalently attached to macromolecules. [18][19][20][21][22][23][24] Bioinspired complexes based on ionic complexation of polypeptides and phospholipids have been recently reported using both peptide homopolymers and block copolymers, leading to a rich polymorphism, including lamellar, tetragonal 14,15 or rectangular 14,25 mesophases. Furthermore, in contrast to peptidic polymers covalently modified with mesogenic units, 26,27 polypeptide-surfactant complexes are expected to be pH responsive and thus offer a very promising pathway to design pH-responsive mesostructures.…”
Section: Introductionmentioning
confidence: 99%
“…All dendrons have one specific focal point, which was used for the covalent attachment to the preferred substrate [27][28][29][30][31]. Recently, dendrons have attracted much attention in the area of self-assembly due to their unique assembly characteristics [32][33][34][35]. The ability to modulate both the dendritic generation (size) and composition (chemical structure) endows them with a high degree of tenability [36].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the self-assembly of dendrons with an amphiphilic nature in selective solvents has produced a variety of morphologies such as micelles, vesicles, cylindrical micelles, tubular assemblies and helical ribbons [37][38][39] The self-organization of dendritic building blocks into ordered supramolecular structures has been demonstrated in various conditions such as in a thermotropic fashion in the solid state, in aqueous and organic phases, and at liquid-solid interfaces [40][41][42][43]. For example, Park et al [32] have reported the unique self-assembly characteristics of some amide dendrons. In organic media, these amide dendrons formed thermoreversible supramolecular gels, and then lamella or columnar hexagonal arrays were formed in the dry state depending on the dendron generation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have investigated the self-assembly characteristics of the amphiphilc amide dendrons having peripheral hydrophobic chains, which self-assemble into well-defined structures such as fibers and ribbons in organic solvents by using hydrogen bonding and hydrophobic interactions as a main driving force. [9][10][11][12][13][14][15][16][17][18][19][20] In addition, in aqueous medium, the amide dendrons self-organize into vesicles and cylindrical micelles particularly depending on the nature of the functional group at the focal point of the dendron. 10 Our recent finding of the supramolecular transformation of self-assembled structures from vesicles to nanotubes induced by the host-guest complexation of the focal pyrene group of the amide dendron and cyclodextrins (CDs) 11 highlighted the importance of guiding the self-assembly process of the dendrons through their structural tuning.…”
Section: Introductionmentioning
confidence: 99%